Ijtihad on issue of waqf in malaysia with a special reference to legal authority in administration of waqf property - Hj Ibrahim, Badruddin; Arifin, Mahamad (2015)

(untitled)
Under Islamic law, waqf is a kind of voluntary charitable disposition of wealth. It was practiced since the period of the Prophet (Peace Be Upon Him) and in the following generation until today. In Malaysia, waqf has also been practiced since Islam spread throughout Malaysia. Since then, waqf has become an important instrument of wealth distribution to provide benefit to family members as well as member of society. There are many issues relating to waqf that were developed in Malaysia particularly issues relating to legal authority or power in administration of waqf property, cash waqf, istibdal of waqf property and so forth. This paper focuses on the issue of legal authority or power in administration of waqf property. The question to be examined is to grant an Islamic Religious Council as a sole power to administer waqf property in Malaysia whether it is in line with the spirit and objectives of Islamic law (maqasid al-Shari'ah). Examination extends to analysis whether ijtihad by Malaysian authority on this issue is sound and acceptable as according to the principle of siyasah shar'iyyah that brings benefit to the society. In addition, the paper will finally examine the issue whether there is any room for improvement that can be recommended with respect to administration of waqf in Malaysia. The research is basically qualitative where most of the data will be collected in library. It is hoped that the findings of the research will be able to provide improvement on administration of waqf in Malaysia in the light of the principle of siyasah shar'iyyah.